Outside of Europe - Chaldovich, Boban (Serbia and Montenegro : Wide Open Exposure, 2007)
A critical, short documentary examining the exclusionary nature of EU immigration and border policies and the responsibilities that are placed on periphery countries to handle the flow of migrants and refugees. Ukraine is used as the case study. Far from the eyes of the public, and never seen before on film, the documentary takes the viewer inside the Mukachevo Detention Centre for Women and Children Refugees, as well as the Pavshino Detention Centre for Illegal Migrants and Refugees in Ukraine. Through diverse interviews that include refugees who failed in their attempt to cross into the EU, as well as officials such as the Immigration Minister for the Transcarpathia region, 'Outside of Europe' throws light on various human rights issues that result from the expansion of the European Union.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films